Olfaction in Eating Disorders and Abnormal Eating Behaviour: A Systematic Review - Mohammed Anisul eIslam (Frontiers in Psychology, 2015)
The study provides a systematic review that explores the current literature on olfactory capacity in abnormal eating behavior to present a basis for discussion on whether research in olfaction in eating disorders may offer additional insights with regard to the complex etiopathology of ED and abnormal eating behaviors. Electronic databases (Medline, PsycINFO, PubMed, Science Direct and Web of Science) were searched using the components in relation to olfaction and combining them with the components related to abnormal eating behavior. Out of 1,352 articles, 14 articles were selected (820 patients and 385 control participants) for this review. The highest number of existing literature on olfaction in ED were carried out with AN patients (78.6%) followed by BN (35.7%) and obesity (14.3%). The general findings support that olfaction is altered in AN and Obesity and indicates towards there being no differences in olfactory capacity between BN patients and the general population. Due to the limited number of studies and heterogeneity this review stresses on the importance of more research on olfaction and abnormal eating behavior.